The Civil Works Administration, 1933-1934 : the Business of Emergency Employment in the New Deal. - Schwartz, Bonnie Fox, 1945- (Princeton legacy library., 2014)
Bonnie Fox Schwartz examines the New Deal's Civil Works Administration, the first federal job-creation program for the unemployed. Challenging assumptions that social workers and other urban liberals dominated New Deal relief agencies, she describes the role of engineers and industrial managers in the CWA's employment of 4.2 million Americans during the winter of 1933-1934. Originally published in 1984. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton.